2020
DOI: 10.3346/jkms.2020.35.e375
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Olfactory and Gustatory Dysfunction in COVID-19 Patients in a Quarantine Facility

Abstract: Background Olfactory and gustatory dysfunction has been reported as characteristic symptoms of coronavirus disease 2019 (COVID-19). This study evaluated olfactory and gustatory dysfunction in mild COVID-19 patients using validated assessment methods. Methods A prospective surveillance study was conducted for mild COVID-19 patients who were isolated at the Gyeonggi International Living and Treatment Support Center (LTSC), Korea. Olfactory function was assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…Murat et al, 2020;Nakagawa et al, 2020Nakagawa et al, , 2020Nakakubo et al, 2020;Nakanishi et al, 2020;Noh et al, 2020;Otte et al, 2020;Ozcelik Korkmaz et al, 2020;Paderno et al, 2020;Patel et al, 2020;Perlman et al, 2020;Petersen et al, 2020;Petrocelli et al, 2020bPetrocelli et al, , 2020aPinna et al, 2020;Printza et al, 2020Printza et al, , 2021Qiu et al, 2020;Rajkumar et al, 2020;Ramteke et al, 2020Ramteke et al, , 2020Rojas-Lechuga et al, 2020;Roland et al, 2020;Romero-Sanchez et al, 2020; Rubel et al, 2020;Sakalli et al, 2020;Salepci et al, 2020;Sayin et al, 2020aSayin et al, , 2020bSchirinzi et al, 2020;Schmithausen et al, 2020;Seo et al, 2020;Shoer et al, 2020;Sierpinski et al, 2020;Smith et al, 2020;Somekh et al, 2020; Speth et al, 2020;Spinato et al, 2020;Stavem et al, 2020; Sun et al, 2020;Teklu et al, 2020;Tham et al, 2020;Tsivgou...…”
unclassified
“…Murat et al, 2020;Nakagawa et al, 2020Nakagawa et al, , 2020Nakakubo et al, 2020;Nakanishi et al, 2020;Noh et al, 2020;Otte et al, 2020;Ozcelik Korkmaz et al, 2020;Paderno et al, 2020;Patel et al, 2020;Perlman et al, 2020;Petersen et al, 2020;Petrocelli et al, 2020bPetrocelli et al, , 2020aPinna et al, 2020;Printza et al, 2020Printza et al, , 2021Qiu et al, 2020;Rajkumar et al, 2020;Ramteke et al, 2020Ramteke et al, , 2020Rojas-Lechuga et al, 2020;Roland et al, 2020;Romero-Sanchez et al, 2020; Rubel et al, 2020;Sakalli et al, 2020;Salepci et al, 2020;Sayin et al, 2020aSayin et al, , 2020bSchirinzi et al, 2020;Schmithausen et al, 2020;Seo et al, 2020;Shoer et al, 2020;Sierpinski et al, 2020;Smith et al, 2020;Somekh et al, 2020; Speth et al, 2020;Spinato et al, 2020;Stavem et al, 2020; Sun et al, 2020;Teklu et al, 2020;Tham et al, 2020;Tsivgou...…”
unclassified
“…Seo et al . [ 14 ] also observed olfactory and gustatory dysfunction in around 24.2% of positive patients presenting with mild SARS-CoV-2 infection in their study. Evidence has also suggested that 95.8% of infected hosts of SARS-CoV-2 infection present with symptom of anosmia.…”
Section: Discussionmentioning
confidence: 71%
“…In particular, our authors published an article on 62 mild COVID-19 patients who were isolated in the Gyeonggi International Living and Treatment Support Center (LTSC) during the early stage of the pandemic (May 2020), reporting that 24.2% and 17.7% complained about subjective olfactory and gustatory dysfunction, respectively. Furthermore, when we performed an objective olfactory function evaluation using the Cross-Cultural Smell Identification Test (CC-SIT), we confirmed that all patients with reported olfactory dysfunction had a reduced sense of smell [ 6 ].…”
Section: Introductionmentioning
confidence: 85%
“…Last year, we published an article about the trend of olfactory dysfunction in mild COVID-19 patients. In this study, we reported that COVID-19 infection-associated olfactory dysfunction was regarded as having a sensory neural cause, characterized by a quantitative disorder (reduced or absence of olfaction), such as post-infectious olfactory dysfunction [ 6 ]. In the case of post-infectious olfactory dysfunction, the optimal treatment strategies remain unclear.…”
Section: Introductionmentioning
confidence: 99%